The Environment Modifies the Relationship Between Social Networks and Secondhand Smoke Exposure Among Korean Nonsmokers in Seoul and California. (March 2015) - Allem, Jon-Patrick; Ayers, John W.; Unger, Jennifer B.; Vollinger, Robert E.; Latkin, Carl; Juon, Hee-Soon; Park, Hae-Ryun; Paik, Hee-Young; Hofstetter, C. Richard; Hovell, Melbourne F.
This study compared risks of secondhand smoke exposure (SHSe) among Korean nonsmokers in Seoul, South Korea and California, United States. Social networks were hypothesized to contain more smokers in Seoul than in California, and smokers were hypothesized to produce more secondhand smoke in Seoul than California, as Seoul's policies and norms are less restrictive. Telephone interviews were conducted with Korean adults in Seoul (N = 500) and California (N = 2830). In all, 69% (95% confidence interval [CI] = 64-74) of Koreans and 31% (95% CI = 29-33) of Korean Americans reported any SHSe. A total of 44% (95% CI = 40-47) of Korean family members smoked versus 29% (95% CI = 28-30) of Korean American family members ( t = 7.84, P < .01). A 25% to 75% increase in the proportion of family members that smoked corresponded with a 13% (95% CI = 5-21) higher probability of any SHSe among Koreans compared with 6% (95% CI = 2-10) among Korean Americans. Network interventions in combination with policies and/or health campaigns may help reduce SHSe globally.